Assessing the Role of Digital Marketing, Content Strategy, and Customer Interaction in Driving Sales Volume in the Café Industry - Situmorang, Soraya Agustina (ProBisnis : Jurnal Manajemen, 2025)
This study analyzes the influence of digital marketing, content strategy, and customer interaction on sales volume within the café industry. Using a quantitative method and survey data from café businesses, the research evaluates how each variable contributes to overall sales performance. Results show that all three factors have a statistically significant impact, with customer interaction proving to be the most dominant. The coefficient of determination (R² = 0.672) indicates that a substantial portion of sales variation can be explained by the model. These findings underscore the importance of building a strong digital presence, delivering engaging content, and maintaining consistent interaction with customers. From a practical perspective, cafés are encouraged to optimize their digital efforts, especially via social media, to strengthen customer relationships and drive sales growth. This study also offers relevant insights for further exploration of digital strategies in the food and beverage industry